Education through sport with the principle of fair play in pre-war Łódź – a city of cultural differences - Jolanta Kowalska; Piotr Kędzia (Studia z Teorii Wychowania)
The educational aspects of sports were recognized during the development of sports along with its educational values, character formation, including the adherence to the fair play principle, primarily in English schools. Pierre de Coubertin, the founder of the modern Olympic Games, based his philosophy of Olympism on them, aiming for the development of athletes from different nations. Łódź, a multicultural place – a "small center of games" at the turn of the 19th and 20th centuries, was such a place. Sport and various forms of physical activity were the foundation for bringing together people from different social, cultural, and religious backgrounds in this rapidly growing industrial city.The Western European genealogy of fair play contains elements of medieval chivalric ethos, ethical virtues of Renaissance courtiers, and the moral ideals of a 19th-century English gentleman. The supplement to the fair play idea also includes the ethical sports contexts present in the histories of local sports communities. The overview of selected documents presented in this article testifies to the significant role of sport, along with the fair play principle, in the creation of a common, multicultural, industrial city. It also encourages a brief presentation of pioneering actions aimed at popularizing sports with the fair play principle during the development of Łódź.